Medium-term risk of recurrent pelvic organ prolapse within 2-year follow-up after laparoscopic sacrocolpopexy - Hirotaka Sato; Shota Otsuka; Hirokazu Abe; Tomoaki Miyagawa (Wolters Kluwer Medknow Publications, 2023)
Objective: The present study was performed to determine the risk of recurrent pelvic organ prolapse (POP) within 2 years after laparoscopic sacrocolpopexy (LSC) in patients with uterovaginal prolapse. Materials and Methods: A retrospective comparative study was performed in a population of 204 patients over a 2-year follow-up period following LSC with concomitant supracervical hysterectomy or uterine preservation at a single urological clinic between 2015 and 2019. The primary outcome was surgical failure following LSC in cases of POP, focusing on failures occurring before the 2nd year of follow-up. Logistic regression analysis was used to determine the odds ratios (ORs) for surgical failure. Results: The primary outcome, surgical failure in cases of POP, occurred 2 years after the initial surgery in 19 of the 204 patients (9.3%) (95% confidence interval [CI], 5.7% - 14.2%). Surgical failure was most common in the anterior compartment (n = 10, 4.9%), and further surgery was performed in seven of the patients with surgical failure (3.4%). The poor primary outcome was predicted by lysis of adhesions (OR, 7.5, 95% CI, 1.6-33.8, P = 0.008) and preoperative POP stage IV (OR, 3.5; 95% CI, 1.1-10.8, P = 0.03) on multivariable logistic regression analysis. Conclusion: The overall rate of surgical failure following LSC in our cohort was 9.3% over the 2-year follow-up period after surgery, and preoperative prolapse stage IV was associated with a higher risk of recurrence.